2020
DOI: 10.3390/nano10061118
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Titanium Dioxide Nanoparticles (TiO2NPs) on Cadmium Chloride (CdCl2) Genotoxicity in Human Sperm Cells

Abstract: The environmental release of titanium dioxide nanoparticles (TiO2NPs) associated with their intensive use has been reported to have a genotoxic effect on male fertility. TiO2NP is able to bind and transport environmental pollutants, such as cadmium (Cd), modifying their availability and/or toxicity. The aim of this work is to assess the in vitro effect of TiO2NPs and cadmium interaction in human sperm cells. Semen parameters, apoptotic cells, sperm DNA fragmentation, genomic stability and oxidative stress were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…Nano-TiO 2 can cause genotoxicity [ 41 ]. Furthermore, the ROS-mediated stress within cells could be the main mechanism for the genotoxicity of nano-TiO 2 [ 42 ]. Further studies are needed to explore whether the TiO 2 NPs and NTs can jointly cause DNA damage due to the production of ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Nano-TiO 2 can cause genotoxicity [ 41 ]. Furthermore, the ROS-mediated stress within cells could be the main mechanism for the genotoxicity of nano-TiO 2 [ 42 ]. Further studies are needed to explore whether the TiO 2 NPs and NTs can jointly cause DNA damage due to the production of ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our study investigated the potentially antigenotoxic functions of EA, an antioxidant compound poorly studied in seminal fluid. In this study, human sperm cells were exposed in vitro to EA to investigate its potential in contrasting the genotoxic effect of benzene (Santonastaso et al, 2020). First, we observed that sperm DNA integrity was not affected by EA incubation, regardless the length of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic pattern generated by the RAPD‐PCR profiles allowed the calculation of the genomic template stability (GTS%) as follows: GTS% = (1 − a/ n ) × 100, where a is the average number of polymorphic bands detected in each exposed sample, and n corresponds to the number of total bands in the nontreated cells. The template genomic stability of control was set to 100% (Santonastaso et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to cadmium causes destructive effects in male and female reproductive systems and negatively affects on sperm parameters (Kumar & Sharma, 2019; Pollack, Ranasinghe, Sjaarda, & Mumford, 2014; Zhao et al, 2017). Previous studies showed that cadmium induces DNA fragmentation during apoptosis in various cells in vitro and in vivo (Acosta et al, 2016; El‐Atta et al, 2014; Santonastaso et al, 2020). Also, it was emphasised that cadmium exerts its toxic effects through induction of oxidative stress (Xia, Chen, Dahms, Ying, & Peng, 2016).…”
Section: Introductionmentioning
confidence: 98%